2014
DOI: 10.1103/physrevb.89.020402
|View full text |Cite
|
Sign up to set email alerts
|

Hidden magnetic order in Sr2VO4clarified withμ+SR

Abstract: In order to elucidate the magnetic ground state of Sr 2 VO 4 , we have measured muon spin rotation and relaxation (μ + SR) spectra of a powder sample in the temperature range between 1.8 and 140 K. As a result, we have clarified that the transition at 105 K is not magnetic but structural and/or electric in origin and found the appearance of static antiferromagnetic (AF) order below 8 K. Moreover, the distribution of the internal AF field was found to be very broad, even at the lowest temperature measured. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 22 publications
5
21
0
Order By: Relevance
“…11,12 These results suggest that the spin-orbital ordering state, which was proposed by first-principles calculation studies by Imai et al 14,15 , appeared below T c0 . On the basis of the theoretical studies, we can expect a severe competition between many types of spin-orbital ordering patterns due to the coexistence of ferromagnetic and antiferromagnetic correlations and the associated effect of frustration.…”
Section: 9supporting
confidence: 59%
“…11,12 These results suggest that the spin-orbital ordering state, which was proposed by first-principles calculation studies by Imai et al 14,15 , appeared below T c0 . On the basis of the theoretical studies, we can expect a severe competition between many types of spin-orbital ordering patterns due to the coexistence of ferromagnetic and antiferromagnetic correlations and the associated effect of frustration.…”
Section: 9supporting
confidence: 59%
“…We find here that indeed the crystal-field levels are reversed in α-Sr 2 CrO 4 , regardless of the elongation of the CrO 6 octahedron examined, which is in sharp contrast to the case of α-Sr 2 VO 4 . [18][19][20] We also examined the electronic state of LaSrVO 4 , which has the same crystal structure with the 3d 2 electron configuration; 21,22) only the antiferromagnetic phase transition was observed experimentally. 8,23) Our DFT calculation shows that the reversal of the crystal-field levels does not occur in this material.…”
Section: -3)mentioning
confidence: 99%
“…Indeed, magnetic properties, such as the magnitude of the drop and absolute value of magnetic susceptibility even at high temperatures, depended strongly on samples as seen in reference [8]. We recently succeeded in establishing the synthesis method of the compound, and found that magnetic dipole order appears only below T N ∼8 K [9]. This fact naively seems to support the nontrivial order, but the magnetic octupole order has not been ruled out, because inelastic neutron scattering measurements have revealed the excitation between the Kramers doublets expected by the spin-orbit coupling [10].…”
Section: Introductionmentioning
confidence: 96%
“…This is a part of proceedings of ICM 2015, where magnetic properties of isostructural Sr 2 CrO 4 will be presented together with those of the V compound. In this paper, the characterization of the phase transitions of the latter compound is focused because the other parts of the presentation have already been reported elsewhere [9,11].…”
Section: Introductionmentioning
confidence: 99%